Climate change-induced migration: a bibliometric review - Juan Milán-García; José Luis Caparrós-Martínez; Nuria Rueda-López; Jaime de Pablo Valenciano (BMC, 2021)
Abstract Background This paper has reviewed the international research on the terms "climate change" and "human migration" from 1999 to 2019. To this end, a bibliometric and a cluster analysis by fractional accounting have been carried out using two of the most important databases: Web of Science (WoS) and Scopus. The research found and studied 140 documents from WoS Core Collection and 193 from Scopus. Results The results show a continual increase in the number of articles published and citations received during the whole period studied. The U.S., U.K., Germany and China have been shown to be the most productive countries and there is a predominance of North American organizations supporting and fostering research on these topics. Conclusions The main contribution of this article is the analysis of new tendencies. The trend shows a transition from concepts such as vulnerability, climate change, land degradation, refugees and security to others such as concepts such as international migration, climate justice, sustainability, human rights and disaster risk reduction. Future research in this field should address the comparison of results from research focused on human beings to a focus on other living beings.